CONTRASTIVE ANALYSIS OF INTERROGATIVE SENTENCES IN ENGLISH AND MANDARIN LANGUAGE - JUNIAR .; RIDWAN SYAHPUTRA (JURNAL ILMIAH MAKSITEK, 2019)
This Thesis is entitled A Contrastive Analysis of Interrogative Sentences of English and Mandarin Language that focused in the analysis of the contrastive of interrogative sentences between English and Mandarin languages especially in the Question Words. Contrastive Analysis is the technique for determining the similarities and dissimilarities between two or more languages with the principal aim of the pinpointing their implications for language teaching and learning. By investigating the mapping of the question words onto the grammatical level, this research looks at both function and aims at discovering some of the factors that influence the forming interrogative sentences. The writer collects and analyzes interrogative sentences from the question words in some book and interviews some native speakers of English and Mandarin language. The theories used to analyze is about interrogative pronouns, interrogative adjectives and interrogative adverbs. The purpose of this research is to find the formation of interrogative sentences in English and Mandarin and to find out the similarities and dissimilarities between English and Mandarin interrogative sentences. The result of this research are expected to (1) provide insight into similarities and dissimilarities between Mandarin and English question words for other researchers and the readers, (2) to provide some information as well as useful contribution for the students and the teacher in department of English, (3) to give detailed description of the similarities and dissimilarities between languages contrasted to teachers who indulge in teaching foreign languages. The writer realises this thesis is still far from perfect. Therefore, every suggestion, criticism are well accepted and highly appreciated.